Proba the Prophet : the Christian Virgilian Cento of Faltonia Betitia Proba - Cullhed, Sigrid Schottenius. (Mnemosyne, Supplements, 2015)
In Proba the Prophet: The Christian Virgilian Cento of Faltonia Betitia Proba Sigrid Schottenius Cullhed offers an in-depth study and reappraisal of the Cento of Proba and its reception. Proba's poem belongs to the few extant Latin texts from Antiquity penned by a woman writer, and one of the oldest Christian Latin poems. Schottenius Cullhed surveys and challenges common preconceptions and biographical constructions of the poem's author and early readers, and examines their impact on interpretations and evaluations of the text. The author also develops and puts to use an alternative model for understanding the poem and convincingly shows how the Virgilian source texts form a complex net of internal and external biblical typologies within the Cento .